Effects of exposure length, cortical and trabecular bone contact areas on primary stability of infrazygomatic crest mini-screws at different insertion angles - Bingran Du; Yuan Lin; Mohan Ji; Qiaohua Yang; Jiang Jiang; Fei Wang; Xiaoyi Wang; Jinchuan Tan; Rui Jia; Jianyi Li (BMC, 2024)
Abstract Background The infrazygomatic crest mini-screw has been widely used, but the biomechanical performance of mini-screws at different insertion angles is still uncertain. The aim of this study was to analyse the primary stability of infrazygomatic crest mini-screws at different angles and to explore the effects of the exposure length (EL), screw-cortical bone contact area (SCA), and screw-trabecular bone contact area (STA) on this primary stability. Methods Ninety synthetic bones were assigned to nine groups to insert mini-screws at the cross-combined angles in the occlusogingival and mesiodistal directions. SCA, STA, EL, and lateral pull-out strength (LPS) were measured, and their relationships were analysed. Twelve mini-screws were then inserted at the optimal and poor angulations into the maxillae from six fresh cadaver heads, and the same biomechanical metrics were measured for validation. Results In the synthetic-bone test, the LPS, SCA, STA, and EL had significant correlations with the angle in the occlusogingival direction (r LPS = 0.886, r SCA = -0.946, r STA = 0.911, and r EL = -0.731; all P < 0.001). In the cadaver-validation test, significant differences were noted in the LPS (P = 0.011), SCA (P = 0.020), STA (P = 0.004), and EL (P = 0.001) between the poor and optimal angulations in the occlusogingival direction. The STA had positive correlations with LPS (r s = 0.245 [synthetic-bone test] and r = 0.720 [cadaver-validation test]; both P < 0.05). Conclusions The primary stability of the infrazygomatic crest mini-screw was correlated with occlusogingival angulations. The STA significantly affected the primary stability of the infrazygomatic crest mini-screw, but the SCA and EL did not.